Green Vehicles For Sustanability In Support For Smart City Development - Suryono, Bisma; andriansyah, Bedy; Felisya Purnama, Devira (International Journal of Science, Technology & Management, 2024)
Green vehicles are vehicles that produce less harmful impacts to the environment than vehicles that use conventional internal combustion comparable to gasoline or diesel, or that use certain alternative fuels. Green vehicles consist of electric, hydrogen and hybrid. Where this green vehicle will help develop and advance smart cities. This research aims to Support the sustainability of Smart City Development and provide Innovation to research and develop green vehicles that are low emission and Dependent on renewable energy or renewable energy. This research was carried out by qualitative methods. By focusing on the sustainability of green vehicles to support smart cities.